Retail Practice of Pertalite Fuel in Small-Scale Sales: A Perspective from Islamic Law and Presidential Regulation No. 117 of 2021 - Kasri; Haeran; Alisyah Pitri (Zabags Qu Publish, 2025)
This study examines the retail sale of Pertalite fuel in Kelurahan Kampung Singkep from the perspectives of Islamic law and Presidential Regulation No. 117 of 2021. The phenomenon arises from limited public access to official fuel stations and local economic needs that give rise to informal retailing practices. Employing a qualitative phenomenological approach, the research draws on interviews, participant observation, and documentary evidence involving retailers, consumers, and community leaders engaged in these transactions. Findings indicate that small-scale Pertalite retailing operates without formal authorization, relies on simple informal distribution mechanisms, and reflects generally low legal awareness among participants. From the standpoint of Islamic jurisprudence, such transactions may be permissible when they meet standards of fairness, transparent measurement, and mutual consent, yet they risk involving gharar (uncertainty) where ownership and distribution legitimacy are unclear. Under positive law, these practices conflict with Perpres No. 117/2021, which reserves distribution and retailing of designated fuel types to authorized entities. The study contributes to Islamic economic jurisprudence and public policy debates by highlighting the need to reconcile normative fiqh principles with pragmatic regulatory frameworks to ensure equitable, legal, and accessible fuel distribution for underserved communities.